RELACION ESPECIES-AREA DE ARTROPODOS EN CIMAS DE MONTAÑAS - Covarrubias, R.; Elgueta, M. (Acta Entomológica Chilena, 2022)
In the Chilean Coastal range cióse to Santiago (Región Metropolitana) there exist four isolated mountain tops with elevations over 1.900 m. These summits or tops show an Andine-type of coid steppe vegetation which may be reasonably considered as isolated island-habitats. A species-area research was carried out in these areas for Tenebrionidae and Curculionidae (Coleóptera), and in order to compare, homologous sites in the Andes range were also studied. Exhaustive search and collecting was made in every place on many different occasions. Total areas of the searched systems were measured as the areas comprised by the 1900 isolines in 1/50.000 charts. Significant and positive correlations were found between the number of species and the total areas of the mountain top the systems for both families of beetles. The valúes found for the exponential equation between species/area show z valúes similar to other taxa in island type studies. If distances are taken from the habitat-islands to the Andes range, then a significant and negative correlation is found only for Tenebrionid species. Otherwise no significant correlations were found between distances or higher communication points between tops, either with the number of common species or the difference between number of species in the respective possible pair of mountain tops. A kind of insular-type equilibrium number of species is suggested for the set of mountain tops studied, for both families of beetles.